A biotic perspective on the Oligo-Miocene evolution of the Maldives carbonate platform from forward stratigraphic modelling (Indian Ocean). (November 2022) - Van der Looven, Thomas; Winterleitner, Gerd; Betzler, Christian; Mutti, Maria
Abstract: Forward stratigraphic modelling is a fast-developing modelling approach, used to test conceptual models, and predict stratigraphic architecture and depositional facies from basin to reservoir scales. Published subsurface applications demonstrate its added value by integrating multidisciplinary data as well as geological concepts into its constraints. When applied to carbonate depositional systems, composed of multiple sediment factories, the co-operating and interdependent production mechanisms remain poorly studied. By applying the technique to a well-studied section of the Maldives carbonate platform, a specific model design—adapted to the geological age and setting, and constrained by available data—sheds light on the interaction of its carbonate producers. The results yield a naturalistic depositional facies distribution and offer insight in the changing relationship between biotic communities during the platform evolution. After calibration, the reference model unequivocally links the formerly proposed genetic model to the seismostratigraphic architecture. Furthermore, the results show how environmental changes (seemingly of secondary impact compared to changes in physical accommodation in the stratigraphic record) can induce substantial fluctuations in carbonate production rates of biotic communities, affect the ecological accommodation, and thus impact the platform architecture. Therefore, it is crucial to treat carbonate production rates during periods of environmental change as variables with associated uncertainties in a forward stratigraphic model setup. Highlights: Forward stratigraphic modelling is applied for the first time to a section of the Oligo-Miocene Maldives carbonate platform. Late Oligocene platform drowning occurred under reduced carbonate production conditions. Carbonate production rates cannot be assumed continuous over time intervals with environmental changes. Subdividing the carbonate factory in ecological assemblages provides a biotic perspective on platform sequence stratigraphy.